Villa Kjærholm 1:40 - (:unkn) unknown (Chalmers tekniska högskola / Institutionen för arkitektur och samhällsbyggnadsteknik, 2022)
Wooden model scale 1:40 Villa Kjaerholm was built in 1962 at Rungstedt coast in Denmark. The building is Hannes second project in her career and is a 145 sqm villa with a visible construction and a simple, minimalistic design of wood and bricks. The interior is created by her husband Poul, who made all furniture especially designed for their home. The house was inspired by a pergola and the Japanese concept of “borrowing the landscape”. Hanne wanted the combination of open facades, closeness to the sea and the green surroundings to create a “zen” vibe in the house. MATERIAL The building is constructed with stained wood and white painted bricks that is visible through the inside and outside. The contrast between warm and cold material creates a balance and a minimalistic atmosphere in the house. The flat roof has an edge of oxidized chopper and an upper side made of sedum that ties the building together with the surrounding greenery.
Villa Kjærholm 1:40